Psychiatric mental health nursing : an interpersonal approach - Jones, Jeffrey S.; Beauvais, Audrey Marie (Burlington, MA : Jones & Bartlett Learning, 2023)
"Psychiatric Mental Health Nursing emphasizes interpersonal relations as the foundation for nursing practice and the cornerstone for relationship-based care. Starting out with an important historical overview of the profession, the student is introduced to the rich history of psychiatric mental health nursing. This text then guides the nursing student through the essential phases of self-discovery while integrating interpersonal nursing theory concepts into practice with various populations"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Psychiatric Nursing; Nurse-Patient Relations; Mental Disorders -- Nursing